(untitled) (Research, Society and Development, 2022)
Objectives: To evaluate the effect of passive mobilization on the cardiorespiratory parameters of preterm neonates in a neonatal intensive care unit (NICU). Methods: Preoperative intervention study evaluating 27 preterm infants admitted to NICU in a teaching hospital in the city of Santa Cruz do Sul – RS, from September 2016 to May 2017. The intervention consisted of 15 minutes of passive mobilization with flexion and extension of upper and lower limbs, and dissociation of pelvic girdle. Heart rate (HR), respiratory rate (RR) and peripheral oxygen saturation (SpO2) were assessed before and after each intervention, and pain intensity was evaluated through the Neonatal Infant Pain Scale (NIPS) and respiratory distress through the Silverman Andersen respiratory severity score (SAS). Results: Preterm neonates (n= 27; males, n= 16) with a gestational age of 30.3 ± 2.8 weeks, corrected gestational age of 34.5±1.6 weeks, weight of 1.62±0.4 kg and height of 40 (39-43) cm. There was a reduction in HR (p= 0.006) and an increase in SpO2 (p<0.001) without pain, respiratory discomfort and change in RR after passive mobilization. Conclusion: Passive mobilization significantly reduced heart rate, increased peripheral oxygenation and did not cause respiratory pain or discomfort in the evaluated neonates.